Gambaran Kualitas Pelayanan Non Akademik pada Prodi Rekam Medis dan Informasi Kesehatan : Overview of Non-Academic Service Quality in Medical Records and Health Information Study Program - Fitria, Annah; Nanda Aula Rumana; Noor Yulia; Laela Indawati (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2025)
This research was conducted to evaluate non-academic services provided by the campus and which are not related to the curriculum in the form of supporting resources (responsiveness, neatness and politeness to officers), campus atmosphere, facilities on campus, and soft skills development. The aim of this research is to determine the characteristics and quality of non-academic services for RMIK Study Program students at Esa Unggul University, Jakarta using the servqual method introduced by Zeithaml, Parasuraman and Berry. The sample in this research was active students from the 2019-2023 class based on parallel and regular classes, totaling 74 students. The research method is quantitative with descriptive analysis using the normality test. The research results obtained from the description of characteristics based on gender are dominated by women, based on age dominated by an average age of 22 years, based on class year dominated by class of 2022 and based on class basis dominated by regular class base. Based on the description of the quality of non-academic services that have been carried out as a whole using the servqual method, students feel satisfied. Even though it was found that there were more Satisfied categories, there are several things that must be paid attention to, especially aspects that have low scores compared to others for the next Campus Image.